Dietary salt exacerbates intestinal fibrosis in chronic TNBS colitis via fibroblasts activation - Amamou, Asma (Sci Rep, 2021)
Intestinal fibrosis is a frequent complication in inflammatory bowel diseases (IBD). It is a challenge to identify environmental factors such as diet that may be driving this risk. Intestinal fibrosis result from accumulation of extracellular matrix (ECM) proteins secreted by myofibroblasts. Factors promoting intestinal fibrosis are unknown, but diet appears to be a critical component in its development. Consumption of salt above nutritional recommendations can exacerbate chronic inflammation. So far, high salt diet (HSD) have not been thoroughly investigated in the context of intestinal fibrosis associated to IBD. In the present study, we analyze the role of dietary salt in TNBS chronic colitis induced in rat, an intestinal fibrosis model, or in human colon fibroblast cells. Here, we have shown that high-salt diet exacerbates undernutrition and promoted ECM-associated proteins in fibroblasts. Taken together, our results suggested that dietary salt can activate intestinal fibroblasts, thereby contributing to exacerbation of intestinal fibrosis. Dietary salt may be considered as a putative environmental factor that drives intestinal fibrosis risk.